(untitled) (Mustansiria Dental Journal, 2019)
Background: Acute lymphoblastic leukemia is fast growing cancer of the white blood cell. Chemotherapy which has been used to treat malignant conditions has a negative impact on oral health condition among cancer patients. This observational study was conducted to determine the level of selected salivary physicochemical characteristics including flow rate and total antioxidant) in addition to evaluation of oral health status (dental plaque and gingival health condition) among a group of patients with acute lymphoblastic leukemia. Materials and methods: The present study included thirty patients with acute lymphoblastic leukemia aged (14-17) years old. Those patients attended Medical City in Baghdad and were admitted to the Hematological Center at Teaching Baghdad Hospital. All patients fullfitted certain inclusion criteria. Salivary sample collection and oral examination were carried at three visits: the first visit was carried out before receiving chemotherapy (at the day of admission)(baseline data), while the second visit was carried out at the day 15 (after starting chemotherapy), and the third visit was done at the day 30 (after starting chemotherapy). Stimulated salivary samples were collected and salivary flow rate was determined. Dental plaque was assessed according to criteria of plaque index by Sillness and Lӧe (1964) and gingival health condition was assessed according to the criteria of Modified Gingival Index for Lobene et al (1986). Salivary samples then were chemically analyzed for the detection of salivary total antioxidant. Results: In this study, salivary flow rate decreased with time (visits) (1.44±0.14, 1.27±0.16, 1.02±0.53) with statistically highly significant differences (p<0.01). On the other hand, the mean values of plaque and gingival indices increased with time (visits) (0.89± 0.39, 1.22± 0.58, 1.82 ±0.75) (0.98± 0.49, 1.13± 0.46, 1.38 ±0.84) respectively and the differences were statistically highly significant (p<0.01). While salivary total antioxidant decreased with time (visits) (0.94±0.25, 0.92±0.21, 0.82±0.21) with statistically significant differences (p<0.05). Conclusion: Acute lymphoblastic leukemia, its treatment and duration of treatment have direct and indirect impact on the oral health status of leukemic patients. Those patients had poor oral hygiene with high rate of gingivitis in addition to change in salivary physicochemical properties, thus, an organized, comprehensive oral health preventive and educational programs in addition to intense oral hygiene program before and during the first month of treatment with cytotoxicdrug (chemotherapy) are essential to improve their oral health condition and prevent oral problems and complications.